Roles of mobile genetic elements and biosynthetic gene clusters in environmental adaptation of acidophilic archaeon Ferroplasma to extreme polluted environments - Li, Yiran; Ma, Liyuan; Huang, Shanshan; Chen, Shiqi; Begum, Shadab; Ibrahim, Nazidi; Liang, Yili; Liu, Xueduan (Frontiers in Microbiology, 2025)
Acid mine drainage (AMD), characterized by high concentrations of heavy metals and strong acidity, presents a significant challenge in environmental remediation. The acidophilic archaeon Ferroplasma facilitates soluble electron shuttles secreting and iron precipitate formation to immobilize heavy metals and demonstrating significant remediation capabilities in microbial consortia. However, its environmental adaptation mechanisms in highly polluted environments during remediation remain unclear. Biosynthetic gene clusters (BGCs), which encode specialized metabolites with ecological roles, and mobile genetic elements (MGEs), known to mediate genomic function through gene disruption, rearrangement, and regulatory interference, represent crucial evolutionary means for environmental adaptation. In this study, Ferroplasma acidiphilum ZJ was screened from the traditional AMD of the Zijinshan copper mine, China. Then, it was sequenced, annotated and compared to three other sequenced Ferroplasma strains focusing on the distribution and function of genes concerning MGEs and BGCs. Genome-wide analysis indicated that MGEs, especially IS4 family insertion sequences (ISs) as well as genomic islands (GIs), were located close to functional regions, such as those related to heavy metal translocation, structural stability of cells, and the formation of archaeal ether-linked membranes. Further analysis showed Ferroplasma strains contained over 10 BGCs, with predicted functions spanning antibiotics, exopolysaccharide (EPS), and quorum sensing (QS). The Ferroplasma employed specialized MGEs and BGCs as key environmental adaptation mechanisms. This study provides a genetic framework for understanding the survival strategies of extremophiles in contaminated environments and explores the potential role of archaeal secondary metabolism (SM) in enhancing microbial processes for sustainable AMD bioremediation, by contributing to the detoxification and stabilization of heavy metals typically found in such environments.